SYSTEMATIC LITERATURE REVIEW: FILSAFAT ILMU SEBAGAI BASIS INOVASI DAN PENGEMBANGAN ILMU MANAJEMEN SDM - Abu Qosim Almisfalah; Fitrianingrum Kusumawardhani; Rizal Harun Al Rasyid (PT. Hasba Edukasi Mandiri, 2025)
Philosophy of science can be a critical dialogue partner for the development of science. This is because the philosophy of science is essentially an effort to study philosophical issues related to science. Educational administration as a whole process related to educational activities including direction, planning, coordination, financing, reporting, to supervision in order to cover education. The purpose of this study is to collect and analyze various journals related to the Philosophy of science in relation to educational administration. This study uses the Systematic Literature Review (SLR) method and identifies data sources one by one according to the specified steps and procedures. The results of this study indicate that there is a relationship between the philosophy of science in the context of educational administration for maximum results when applied in educational institutions. By identifying trends, gaps, and potential developments in this field, this study makes a significant contribution to strengthening the philosophical basis in administrative decision-making. In addition, the findings of this study can be a foundation for academics, policymakers, and practitioners to develop a more holistic, contextual, and relevant educational administration model to the challenges of 21st-century education.